Information Economy Report 2005 - United Nations Conference on Trade; Development (United Nations, 2005)
This Report illustrates the vigorous efforts being undertaken by many developing countries to catch up with their more developed partners in the dissemination and use of ICT. However, it also shows that the gaps are still far too wide and the catching-up far too uneven for the promise of a truly global information society, with its attendant benefits for sustainable social and economic development, to materialize without the sustained engagement of national Governments, the business sector and civil society, and the tangible solidarity of the international community.